2021
DOI: 10.1186/s13568-021-01181-0
|View full text |Cite
|
Sign up to set email alerts
|

Phages from Ganges River curtail in vitro biofilms and planktonic growth of drug resistant Klebsiella pneumoniae in a zebrafish infection model

Abstract: Bacteriophages are a promising alternative for curtailing infections caused by multi drug resistant (MDR) bacteria. The objective of the present study is to evaluate phage populations from water bodies to inhibit planktonic and biofilm mode of growth of drug resistant Klebsiella pneumoniae in vitro and curtail planktonic growth in vivo in a zebrafish model. Phage specific to K. pneumoniae (MTCC 432) was isolated from Ganges River (designated as KpG). One-step growth curve, in vitro time kill curve study and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Nevertheless, majority of studies has compared the effect of antibiotics and phage therapy and scarce reports are available that has studied the combination of antibiotic and phage therapy. In our earlier study, we found that the combination of Streptomycin and KpG (Podoviridae phage specific to K. pneumoniae) curtailed the infection by 98% relative to untreated control, whereas KpG alone caused 77% reduction and only streptomycin resulted in 63% reduction in colony counts [39]. In the present study, U1G and colistin + U1G declined the bioburden by 0.8 and 1.4 log, respectively (Figure 7), corresponding to 86% and 95% reduction in bioburden.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Nevertheless, majority of studies has compared the effect of antibiotics and phage therapy and scarce reports are available that has studied the combination of antibiotic and phage therapy. In our earlier study, we found that the combination of Streptomycin and KpG (Podoviridae phage specific to K. pneumoniae) curtailed the infection by 98% relative to untreated control, whereas KpG alone caused 77% reduction and only streptomycin resulted in 63% reduction in colony counts [39]. In the present study, U1G and colistin + U1G declined the bioburden by 0.8 and 1.4 log, respectively (Figure 7), corresponding to 86% and 95% reduction in bioburden.…”
Section: Discussionsupporting
confidence: 61%
“…No phages specific to U1007 were obtained from any other sources tested (Figure S1). We recently reported a phage KpG, belonging to Podoviridae, specific to MDR K. pneumoniae from Ganges, which was able to curtail the host's planktonic and biofilm mode of growth [39]. There are other numerous reports available on rich diversity of bacteriophages against various pathogens being isolated from The Ganges [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, bacteriophages targeting MDR E. coli U1007 were isolated from The Ganges River (designated as U1G), Cooum River (CR) and Hospital Waste water(M) (Figure S1). We recently reported a phage KpG, belonging to Podoviridae, specific to MDR K. pneumoniae from which was able to curtail the host's planktonic and biofilm mode of growth [53]. There are other numerous reports available on rich diversity of bacteriophages against various pathogens being isolated from The Ganges [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a mature innate immune system, zebrafish embryos are genetically similar to human, and their transparency make them ideal for investigating characteristics of infection mechanisms unreachable in standard animal models. Very recently, several zebrafish studies have been published for evaluating phage treatment upon bacterial infections, though none have studied S. aureus (Easwaran et al, 2017;Johansen et al, 2021;Sundaramoorthy et al, 2021). Bacteria can be injected into the embryo's bloodstream alongside phages, and this treatment was effective with a better survival of the infected zebrafish embryos.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%